Hubungan Kualitas Informasi Akun Instagram @warkopsepenuhati dengan Pengetahuan Followers tentang Produk Sepenuhati Kopi - Suwardi, Adi; Saepudin, Encang (JIPI (Jurnal Ilmu Perpustakaan dan Informasi), 2022)
The purpose of this study was to determine the relationship between the quality of information on Instagram @warkopsepenuhati which includes accuracy, time, and the relevance of information with followers' knowledge about the product. This study uses a correlational quantitative method with a sample of 89 people after going through the calculation of the Slovin formula. Questionnaires were used to collect data as primary data in this study. The distribution of the questionnaire was carried out online to the followers of the Sepenuhati Kopi instagram. In addition to questionnaires, data were collected by interview, observation, and literature study as secondary data. The analysis method uses descriptive analysis (respondent data and research data) and inferential analysis (relationship hypothesis testing) processed using SPSS version 25. The results of this study indicate that there is a strong relationship that occurs between the quality of information on the @warkopsepenuhati Instagram account and followers' knowledge about Sepenuhati Kopi products.